Role of LncRNA in Trauma Susceptibility and Resilience to Post-Traumatic Stress Disorder (PTSD): A Pilot Study in the African American Population - Sadhukhan T; Rai N; Misiak-Christian M; Hipolito MMS; Sadhukhan S; Shelby M; Mejía Mondragón CI; Idowu A; Gondringer A; Kalejaiye A; Li J; Islam MN; et al. (Neuropsychiatric Disease and Treatment)
Tamal Sadhukhan,1 Narayan Rai,1 Magdalena Misiak-Christian,2 Maria Mañanita S Hipolito,1 Sriparna Sadhukhan,1 Myeshia Shelby,3 Claudia Ivonne Mejía Mondragón,1 Abimbola Idowu,1 Alix Gondringer,1 Adedoyin Kalejaiye,4 James Li,5 Md N Islam,6 Habtom W Ressom,6 Evaristus A Nwulia1 1Department of Psychiatry and Behavioral Sciences, Howard University, Washington, DC, USA; 2Department of Physiology and Biophysics, Howard University, Washington, DC, USA; 3Department of Genetics, Graduate School, Howard University, Washington, DC, USA; 4Department of Surgery Otolaryngology, Howard University, Washington, DC, USA; 5Department of Biostatistics, Bioinformatics & Biomathematics, Georgetown University, Washington, DC, USA; 6Lombardi Comprehensive Cancer Center, Genomics & Epigenomics Shared Resource, Georgetown University, Washington, DC, USACorrespondence: Evaristus A Nwulia, Department of Psychiatry and Behavioral Sciences, Howard University, Washington, DC, USA, Email enwulia@howard.eduPurpose: Childhood adversities are associated with the development of post-traumatic stress disorder (PTSD). However, not all individuals exposed to severe trauma develop psychopathology, underscoring the need for a better understanding of the molecular pathophysiology underlying vulnerability to PTSD. Evidence suggests that the peripheral olfactory system, which is accessible in the nose, regulates the structure and function of olfactory regions relevant to stress biology. Long non-coding RNAs (lncRNAs) control transcriptional regulation via epigenetic mechanisms, and since these elements are sensitive to environmental inputs, they may play a crucial role in diseases like PTSD, which are highly dependent on environmental experiences. This study aims to identify lncRNAs in the olfactory mucosa associated with vulnerability and resilience to PTSD in African American populations.Patients and Methods: Thirty-eight adult residents in the Washington DC metropolitan region, aged 18– 50 years were recruited based on a history of exposure to trauma during childhood. Participants were divided into three groups: those who experienced childhood trauma and developed PTSD, those with similar trauma but did not develop PTSD, and a control group who did not experience childhood trauma. Olfactory mucosa samples were collected through nasal brushings, and neurobehavioral assessments were conducted. RNA sequencing was performed to facilitate lncRNA-based analysis, exploring differentially expressed lncRNAs among the specified groups.Results: Two lncRNAs, CYP1B1-AS1 and SLC7A11-AS1, known for their neuroprotective and anti-inflammatory functions, were significantly elevated in the PTSD group compared to the non-trauma-exposed controls. Ingenuity Pathway Analysis of the differentially expressed lncRNAs suggests their potential involvement in NFAT5-mediated inflammatory cascades, indicating a possible biological mechanism underlying PTSD vulnerability.Conclusion: PTSD may be associated with epigenetic modifications of inflammatory and immunoregulatory pathways in the olfactory system. Further evaluation of the relationship between these differentially expressed lncRNAs and PTSD should be conducted with larger samples and more diverse cohorts.Keywords: PTSD, lncRNA, CYP1B1-AS1, SLC7A11-AS1, NFAT5